Antibacterial Study of Some Oxazepine Derivatives - Ahmed, Ahmed; Mahdi, Sarah; Hussein, Anwar; Hamed, Ayad; Yousif, Emad (Al-Nahrain Journal of Science, 2018)
Compounds containing 1,3-oxazepine and 1,3,4-oxadiazole (5)-(8) were synthesized by microwave assisted organic synthesis method through the condensation reaction of compounds (1 to 4) with phthalic anhydride respectively. The structure of the synthesized compounds were characterized by spectroscopic methods (1H NMR, FTIR). The synthesized compounds were screened for their antibacterial activity disc diffusion method.